2020
DOI: 10.1186/s12957-020-01890-z
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of CEUS-guided sentinel lymph node biopsy in early-stage breast cancer: a study review and meta-analysis

Abstract: Objective: To investigate whether preoperative localization of sentinel lymph node (SLN) by contrast-enhanced ultrasound (CEUS) can further improve the accuracy of sentinel lymph node biopsy (SLNB). Method: Collect published literatures or conference reports by searching electronic databases. The Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) evaluation method is used to evaluate the quality of the screened literatures. The pooled risk ratio of cancer metastasis of SLN identified by CEUS (CE-SL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…Regarding the number of observed lymph nodes, more lymph nodes were observed with MB than CEUS, which is consistent with the results of some previous studies [ 2 , 18 21 ]. Since MB has a small molecular weight and lymphatic vessels have good absorbency of MB, when it drains to the SLN after injection, there is partial drainage to subsequent lymph nodes other than the SLNs, causing some of the subsequent lymph nodes to be stained blue during the process of intraoperative detection.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Regarding the number of observed lymph nodes, more lymph nodes were observed with MB than CEUS, which is consistent with the results of some previous studies [ 2 , 18 21 ]. Since MB has a small molecular weight and lymphatic vessels have good absorbency of MB, when it drains to the SLN after injection, there is partial drainage to subsequent lymph nodes other than the SLNs, causing some of the subsequent lymph nodes to be stained blue during the process of intraoperative detection.…”
Section: Discussionsupporting
confidence: 92%
“…MB is prone to allergic reactions, local skin flap and adipose tissue necrosis in previous study [ 21 ], and one patient developed localized skin necrosis in our study. No patients had adverse reaction to CEUS in this study.In addition, CEUS can display lymphatic vessels and lymph nodes visually.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…SLN biopsy done by pCEUS, which has been a focus of research over recent years, especially for breast cancer, has shown a promising performance (29). However, only a few studies focused on percutaneous pCEUS in SLN in CMM.…”
Section: Discussionmentioning
confidence: 99%
“…It's been reported that the combination of those 2 methods can significantly increase the success rate of SLN biopsy and reduce its false negative rate. [ 5 , 6 ] The blue dye method currently uses methylene blue more frequently in China, which is simple, economical, and easy to obtain, [ 7 ] but it's been reported to be connected with several adverse complications such as contrast agent extravasation. [ 8 ] The radionuclide method recommends the use of 99mTc-labeled sulfur colloid.…”
Section: Introductionmentioning
confidence: 99%